Optimalisasi Keuntungan D’nanas Dengan Metode Transportasi - Alief Noverdy Chaliandra Putra; Gibran Krisna Athallah; Muhammad Farhan (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study applies the graphical method of transportation programming to optimize production decisions in small and medium enterprises (SMEs) processing pineapples. Tangkit Baru Village, as a case study, produces approximately 22,000 pineapples daily, with SMEs developing derivative products such as soft pineapple candy (PLN) and chocolate-coated pineapple chips. Although resources such as capital, raw materials, and labor are relatively sufficient, the profitability of these derivative products remains lower compared to the sale of fresh pineapples. This research aims to determine the optimal production combination of PLN and KNC that maximizes profit using the graphical method of linear programming. Two decision variables are modeled under the constraints of production time and demand capacity. The results show that a specific combination of PLN and KNC yields a higher overall profit compared to producing a single product. This study highlights the usefulness of the graphical method as a simple yet effective decision-making tool for micro and small enterprises in optimizing product diversification strategies. Keywords: Linear programming, graphical method, optimization, pineapple products, SMEs   Abstrak Penelitian ini menerapkan metode grafis pemrograman transportasi untuk mengoptimalkan keputusan produksi pada usaha mikro, kecil, dan menengah (UMKM) yang mengolah nanas. Desa Tangkit Baru, sebagai studi kasus, menghasilkan sekitar 22.000 buah nanas per hari, dengan UMKM mengembangkan produk turunan seperti permen nanas lunak (PLN) dan keripik nanas berlapis coklat (KNC). Meskipun sumber daya seperti modal, bahan baku, dan tenaga kerja cukup memadai, profitabilitas produk turunan ini tetap lebih rendah dibandingkan dengan penjualan nanas segar. Penelitian ini bertujuan untuk menentukan kombinasi produksi PLN dan KNC yang optimal guna memaksimalkan keuntungan dengan menggunakan metode grafis pemrograman linier. Dua variabel keputusan dimodelkan di bawah kendala waktu produksi dan kapasitas permintaan. Hasil penelitian menunjukkan bahwa kombinasi tertentu antara PLN dan KNC menghasilkan keuntungan keseluruhan yang lebih tinggi dibandingkan dengan memproduksi satu produk saja. Penelitian ini menyoroti kegunaan metode grafis sebagai alat pengambilan keputusan yang sederhana namun efektif bagi usaha mikro dan kecil dalam mengoptimalkan strategi diversifikasi produk.Kata Kunci: Pemrograman linier, metode grafis, optimasi, produk nanas, UMKM